Analisis Pengaruh Indeks Pembangunan Manusia, Tingkat Kesempatan Kerja, Jumlah Penduduk Miskin, Dan Upah Minimum Terhadap Tingkat Pengangguran Terbuka Di Eks Karesidenan Semarang Periode 2017-2021 - Anggie Citra Prastikasari (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2022)
Unemployment is a frequently encountered work issue, all the countries most affected by the unemployment problem, namely developing countries like Indonesia. The purpose of this study is to analyze how human development index, employment opportunities, number of poor people and minimum wage affect the published unemployment rate of the former Semarang Residency over the period 2017-2021. This survey sample was collected from six districts/cities within the old Semarang Residency. This is a quantitative study employing secondary data from the Central Bureau of Statistics (BPS). Using panel data regression, which mixes time series data with cross-sectional data, the data are analyzed. Fixed Effects Model is the chosen model for this investigation (FEM). According to the results of the data study, all factors, i.e. the Human Development Index, work opportunities, number of poverty, and minimum pay, have a substantial influence on the stated unemployment rate in Semarang's former residence region.